Novel Interactome of Saccharomyces cerevisiae Myosin Type II Identified by a Modified Integrated Membrane Yeast Two-Hybrid (iMYTH) Screen. Issue 5 (1st May 2016) - Santiago, Ednalise; Akamine, Pearl; Snider, Jamie; Wong, Victoria; Jessulat, Matthew; Deineko, Viktor; Gagarinova, Alla; Aoki, Hiroyuki; Minic, Zoran; Phanse, Sadhna; San Antonio, Andrea; Cubano, Luis A; et al.
Abstract: Nonmuscle myosin type II (Myo1p ) is required for cytokinesis in the budding yeast Saccharomyces cerevisiae . Loss of Myo1p activity has been associated with growth abnormalities and enhanced sensitivity to osmotic stress, making it an appealing antifungal therapeutic target. The Myo1p tail-only domain was previously reported to have functional activity equivalent to the full-length Myo1p whereas the head-only domain did not. Since Myo1p tail-only constructs are biologically active, the tail domain must have additional functions beyond its previously described role in myosin dimerization or trimerization. The identification of new Myo1p -interacting proteins may shed light on the other functions of the Myo1p tail domain. To identify novel Myo1p -interacting proteins, and determine if Myo1p can serve as a scaffold to recruit proteins to the bud neck during cytokinesis, we used the integrated split-ubiquitin membrane yeast two-hybrid (iMYTH) system. Myo1p was iMYTH-tagged at its C-terminus, and screened against both cDNA and genomic prey libraries to identify interacting proteins. Control experiments showed that the Myo1p -bait construct was appropriately expressed, and that the protein colocalized to the yeast bud neck. Thirty novel Myo1p -interacting proteins were identified by iMYTH. Eight proteins were confirmed by coprecipitation (Ape2, Bzz1, Fba1, Pdi1, Rpl5, Tah11, and Trx2 ) or mass spectrometry (AP-MS) (Abp1 ). The novel Myo1p -interacting proteins identified come from a range of different processes, including cellular organization and protein synthesis. Actin assembly/disassembly factors such as the SH3 domain protein Bzz1 and the actin-binding protein Abp1 represent likely Myo1p interactions during cytokinesis.